Are there laws of innovation? - Lau, Lawrence J.; Xiong, Yanyan (London : World Scientific, 2022)
Beyond real GDP, innovative capacity is an important indicator of the economic strength of a nation. By studying innovative capacity and other indicators of success in innovation across the Group-of-Seven (G7) Countries, the East Asian Newly Industrialised Economies (EANIEs) and Mainland China, this book will systematically establish a positive relationship between innovation outputs and inputs of different economies. In doing so, it seeks to answer the question $1 (Bare there laws of innovation? It seeks to identify the determinants of innovation at the economy-wide level, ascertain whether these determinants are similar across different economies, and find suitable metrics for comparing relative success in innovation across different economies. It concludes that innovation, rather than being a stroke of good fortune, comes from research and development activities conducted over a long period of time, and sheds light on future trends and areas for further research.s
Keywords: Business & Economics / Knowledge Capital; Business & Economics / Research & Development; Law / Intellectual Property / Patent